TISSUE DOPPLEROGRAPHY AND THE ASSESSMENT OF RIGHT HEART STRUCTURE AND FUNCTION IN PATIENTS WITH CHRONIC OBSTRUCTIVE PULMONARY DISEASE - B. Ya. Bart; O. M. Kulbachinskaya; E. N. Dergunova; E. A. Vartanyan (Российский кардиологический журнал, 2014)
Aim. To assess the status of right heart structure and function in patients with mild chronic obstructive pulmonary disease (COPD).Material and methods. The study included 56 COPD patients and 26 healthy volunteers. All participants underwent lung function assessment and echocardiography.Results. Based on the analysis of the Doppler spectrum of transtricuspid flow, the signs of disturbed right ventricular (RV) relaxation were identified. A reduction in the total RV output was detected, based on the assessment of tricuspid annular amplitude and velocity.Conclusion. In patients with mild COPD but without increased pulmonary vascular.